Takhrīj Ḥadīth Ghars Al-Ashjār: Tracing the Greening Spirit Roots in Sunnah Nabawiyyah - Taufiq Hidayat Karim (Al-Bukhari : Jurnal Ilmu Hadis, 2021)
Analyses of the National Disaster Management Agency (BNPB) states that beside weather and environmental typologies, human activities have a significant role in triggering disasters. Quran Surah Al-Rūm verse 41 has justified this idea, and legitimizes that disasters occur because of people’s lack of awareness and self-motivations to take care of the environment. This article seeks to investigate hadith matn to motivate the action of preserving the nature. This article focuses to find out a qualitative hadith in order to gain an appropriate understanding of hadith (fiqh al- ḥadīth). This research is a library research with a content analyses to related documents. In addition, this study applies a simultaneous hadith approach (a simultaneous method) and understanding of thematic hadith (fiqh al-ḥadīth al-mawḍū'i). This paper concludes that the hadith in this question had a quality of hadith ṣaḥīḥ li dzātih and included into mashhūr ḥadīth (popular hadith). This hadith provides a significant role to motivate greening for the preservation of nature.